MODEL PEMBELAJARAN CTL (CONTEXTUAL TEACHING AND LEARNING) TERHADAP HASIL BELAJAR FISIKA SISWA MATERI POKOK ALAT OPTIK - Sari Wahyuni Rozi Nasution (Program Studi Pendidikan Fisika, Institut Pendidikan Tapanuli Selatan, 2020)
This research aims to know whether there is effect of contextual teaching and learning (CTL) to students’ achievement in optical instrument of the X grade students of SMA Negeri 1 Padangsidimpuan. The population of this research is all of X grade students of SMA Negeri 1 Padangsidimpuan, it is 182 students. Sample of this research is taken by using random sampling. It is 36 students. This research was done by using experiment method. The data was analyzed by two steps, they are descriptive analysis and inferential analysis by using t test to know wheter the hypothesis is accepted or rejected by using one group pretest posttest design and to test the hypothesis by using t-test. The result of the research shows that the mean is 83, it is very good category. Based on the calculation in inferential analysis, it is found that t count is 5.79 and if it is compared to t table in 5 % significant, it is found 1.675. It can be seen that t count is greater than t table or (5.79 > 1.675). The hypothesis is accepted. Means that there is significant effect of contextual teaching and learning (CTL) to students’ achievement in optical instrument of the X grade students of SMA Negeri 1 Padangsidimpuan.